ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN LOKASI TERHADAP USAHA DAGANG - Stepanus Sandy; Juwita Atma Nadia Karno; Siti Kholifa Hadiono (CV. Adiba Aisha Amira, 2024)
This research aims to determine differences in clothing business income in the city of Timika, to find out the factors that influence the choice of location for a trading business. The research method used in this research is a descriptive method. This research was conducted by 50 clothing traders. Data collection techniques were carried out using observation and questionnaires. The analytical instruments used are independent sample t test analysis and factor analysis. The results of the research are that there is no difference in clothing business income in Timika City, and the proximity of infrastructure, market (consumer) proximity, and location costs are factors that determine the choice of clothing business location in Timika City.